Emotional Dysregulation and Adaptive Functioning in Preschoolers With Autism Spectrum Disorder or Other Neurodevelopmental Disorders - Davico, Chiara; Marcotulli, Daniele; Cudia, Valentina Francesca; Arletti, Luca; Ghiggia, Ada; Svevi, Barbara; Faraoni, Chiara; Amianto, Federico; Ricci, Federica; Vitiello, Benedetto (Frontiers in Psychiatry, 2022)
Aim: Emotional dysregulation (ED), defined by deficits in the ability to monitor and modulate the valence, intensity, and expression of emotions, is typically expressed with irritability, tantrums, mood fluctuations, and self-harm in young children with autism spectrum disorder (ASD). Although ED does not represent a diagnostic feature of ASD, its manifestations are an important contributor to functional impairment and clinical referral. This study aims to examine the relationship between ED and adaptive functioning in preschoolers clinically referred for ASD or other neurodevelopmental disorders. Methods: A sample of 100 children (74% males, mean age 39.4 + 12.3 months), consecutively referred to a university clinic for neurodevelopmental disorders, received clinical assessments of psychopathology with the CBCL and the Autism Diagnostic Interview-Revised, of ED, with the CBCL-Attention, Anxious/Depressed, and Aggression index (CBCL-AAA), of autism symptom severity with the ADOS-2 Calibrated Severity Score (ADOS-CSS), and of global developmental/cognitive delay (GDD) with the WPPSI-IV or other age-appropriate standardized scales. Adaptive functioning was measured with the ABAS-II. Sixty-five children met DSM-5 criteria for ASD. Multivariate regression models were applied to evaluate the relative contribution of ED, ASD severity and GDD to the ABAS-II general (GAC), conceptual (CAD), social (SAD), and practical (PAD) adaptive functioning domains. Results: Overall (n=100), lower adaptive functioning was associated with higher CBCL-AAA (p = 0.003), higher ADOS-CSS (p < 0.001), and presence of GDD (p = 0.023). In the ASD group (n=65), worse CAD was predicted by GDD (p= 0.016), and worse SAD and PAD by higher ADOS-CSS (p=0.032) and ED (p=0.002). No sex differences were detected in the study variables. Conclusions: Together with the severity of global developmental delay and of autism symptoms, ED is a significant contributor to impairment in adaptive functioning among young children with a neurodevelopmental disorder and, in particular, with ASD. ED could represent a specific target for early interventions aimed at enhancing adaptive functioning in early childhood.